Gut and respiratory microbiota landscapes in IgA nephropathy: a cross-sectional study - Xiaoli Yuan; Jianbo Qing; Wenqiang Zhi; Feng Wu; Yan Yan; Yafeng Li (Renal Failure)
Background IgA nephropathy (IgAN) is intimately linked to mucosal immune responses, with nasopharyngeal and intestinal lymphoid tissues being crucial for its abnormal mucosal immunity. The specific pathogenic bacteria in these sites associated with IgAN, however, remain elusive. Our study employs 16S rRNA sequencing and machine learning (ML) approaches to identify specific pathogenic bacteria in these locations and to investigate common pathogens that may exacerbate IgAN.Methods In this cross-sectional analysis, we collected pharyngeal swabs and stool specimens from IgAN patients and healthy controls. We applied 16SrRNA sequencing to identify differential microbial populations. ML algorithms were then used to classify IgAN based on these microbial differences. Spearman correlation analysis was employed to link key bacteria with clinical parameters.Results We observed a reduced microbial diversity in IgAN patients compared to healthy controls. In the gut microbiota of IgAN patients, increases in Bacteroides, Escherichia-Shigella, and Parabacteroides, and decreases in Parasutterella, Dialister, Faecalibacterium, and Subdoligranulum were notable. In the respiratory microbiota, increases in Neisseria, Streptococcus, Fusobacterium, Porphyromonas, and Ralstonia, and decreases in Prevotella, Leptotrichia, and Veillonella were observed. Post-immunosuppressive therapy, Oxalobacter and Butyricoccus levels were significantly reduced in the gut, while Neisseria and Actinobacillus levels decreased in the respiratory tract. Veillonella and Fusobacterium appeared to influence IgAN through dual immune loci, with Fusobacterium abundance correlating with IgAN severity.Conclusions This study revealing that changes in flora structure could provide important pathological insights for identifying therapeutic targets, and ML could facilitate noninvasive diagnostic methods for IgAN.